Does a water-training macrocycle really create imbalances in swimmers' shoulder rotator muscles? - Batalha, N.; Marmeleira, J.; Garrido, N.; Silva, A. J. (European Journal of Sport Science, 2015)
The continuous execution of swimming techniques may cause muscle imbalances in shoulder rotators leading to injury. However, there is a lack of published research studies on this topic. The aim of this study was to analyze the influence of a competitive swim period on the shoulder rotator-cuff balance in young swimmers. A randomized controlled pretest-posttest design was used, with two measurements performed during the first macrocycle of the swimming season (baseline and 16 weeks). Twenty-seven young male swimmers (experimental group) and 22 male students who were not involved in swim training (control group) with the same characteristics were evaluated. Peak torque of shoulder internal and external rotators was assessed. Concentric action at 1.04 rad s!1 (3 repetitions) and 3.14 rad s!1 (20 repetitions) was measured using an isokinetic dynamometer (Biodex System 3). External/internal rotators strength ratios were also obtained. For both protocols, there were significant training effects on internal rotator strength and external/internal rotator ratios (p à .05). This trend was the same for both shoulders. Within-group analysis showed significant changes from baseline to 16 weeks for internal rotators strength and unilateral ratios of the experimental group. Swimmers` internal rotator strength levels increased significantly. In contrast, a significant decrease of the unilateral ratios was observed. Findings suggest that a competitive swim macrocycle leads to an increase in muscular imbalances in the shoulder rotators of young competitive swimmers. Swimming coaches should consider implementing a compensatory strength-training program.